Stability Analysis Of Delayed Fractional Integro-Differential Equations With Applications Of RLC Circuits - El-Borhamy, Mohamed; Ahmed, Alaa (Journal of the Indonesian Mathematical Society, 2020)
This article presents the stability analysis of delay integro-differential equations with fractional order derivative via some approximation techniques for the derived nonlinear terms of characteristic exponents. Based on these techniques, the existence of some analytical solutions at the neighborhood of their equilibrium points is proved. Stability charts are constructed and so both of the critical time delay and critical frequency formulae are obtained. The impact of this work into the general RLC circuit applications exposing the delay and fractional order derivatives is discussed.